POVERTY DYNAMICS AND AGRICULTURAL PRACTICES FOR ENVIRONMENT CONSERVATION IN RURAL AFRICAN AREA: The case of Adja plateau in southern Benin - (:unkn) unknown (My University, 2008)
The influence of increase in land pressure on agricultural production and the environment is disputed. On one hand the pessimists, mainly represented by MALTHUS (1798), think that land pressure is associated to negative effects on agricultural production and leads to famine and rural exodus. On the other hand the optimists, mainly represented by BOSERUP (1970), think that land pressure is an essential factor for technological change and agricultural intensification. In fact, although in general the demographic and food evolution in Africa presents a Malthusian trend, like the cases of Yatenga in Burkina Faso, Serer district in Senegal and Adja plateau in Benin Republic, it was even though observed some Boserupian evolutions like the cases of Bamileke district in Cameroon and the district of Machakos in Kenya. One wonders if it's still possible to presage in Africa a generalised optimistic evolution of BOSERUP (1970) and in which conditions. This thesis, from a temporal analysis of 122 households on the Adja plateau in the southern Benin, is developing a theoretical intermediary position between MALTHUS theory and that of BOSERUP. It's demonstrating that in land pressure situation, the farmers' welfare state was a determinant of improving agricultural practices development and agricultural productivity improvement. Land pressure does not induce ipso facto technological change and agricultural development. The MALTHUS spectrum and the optimistic vision of BOSERUP represent the extreme situations induced by a higher chronic poverty rate in the first case and a lower chronic poverty rate in the second case. The ongoing situation on the Adja plateau, where chronic poverty rate is estimated at 28.7 %, is that of the Malthusian spectrum. In order that the farmers can develop sustainable agriculture in land pressure situation, it's necessary to alleviate or eradicate chronic poverty among them by facilitating a truly profitable agriculture.
Keywords: African Research